ESTIMASI NILAI WAJAR SAHAM PT. DELTA DJAKARTA TBK - , Jack Narsio Arnesto, S.T.; , Prof. Dr. Eduardus Tandelilin, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study research is to estimate the Fair Market Value of PT. Delta Djakarta Tbk., its shares of stock owned by DKI Jakarta State Government (minority). The analytical tool used in the study were Income Based Approach and the Market-Based Approach. The data used in this research is based on PT. Delta Djakarta Tbk financial statementâs which has been audited by Public Accountant year period from 2007 to 2010, the financial statements 4 (four) companies. All four comparison companies are: PT. Multi Bintang Indonesia Tbk. from Indonesia, Asahi Breweries Ltd and Sapporo Holdings Ltd. from Japan, and Molson Coors Brewing Co. from United Kingdom. The financial statements are then analyzed to determine the condition of the financial fundamentals and calculate the fair market value of shares. PT. Delta Djakarta Tbk. by using the Income Based Approach and Market-Based Approach. Results obtained using both approaches by Minority Discount applying Discount Lack of Control and based on the analysis of the ability of the company's financial fundamentals, then the fair market value of equity of PT. Delta Djakarta Tbk. on December 31, 2010 amounted to the income approach obtained an indication of fair market value of Rp1.886.108.802.000,- and with the market based approach obtained an indication of Rp1.993.432.863.147,-. By providing a weighting of 50 percent of the Discounted Cash Flow Method and 50 percent of the Market Multiple Method, the indication of fair market value of shares (equity), PT. Delta Djakarta Tbk., Before considering the minority discount amounted Rp121.136 per share. The fair market value of minority shares of publicly owned with shares of 4.204.014 shares and apply the minority discount of 30 percent, then the fair market value amounted to Rp357.111.810.277,- or Rp84.945,- per share.